2021
DOI: 10.1111/1346-8138.15824
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of cutaneous adverse events of immune checkpoint inhibitors in a single tertiary center

Abstract: Programmed death 1 (PD‐1)/programmed death ligand 1 (PD‐L1) inhibitors have demonstrated their efficacy in the treatment of various malignancies. Despite their benefits, their immunomodulatory activities can cause unpredictable cutaneous adverse events (CAE). This study aimed to identify characteristics of CAE in patients treated with PD‐1/PD‐L1 inhibitors through the medical records, photographs, and pathology reports. Fifty CAE occurred in 47 (2.75%) of 1711 patients treated with PD‐1/PD‐L1 inhibitors. Pruri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…[ 23 ] A Korean retrospective analysis found that melanoma and genitourinary malignancies were most likely to experience cutaneous adverse reactions following the use of PD-1/PD-L1 inhibitors; pruritic, psoriatic, and urticaria are the most common types of rash, with median times of appearance of 15, 20, and 6.5 weeks respectively; urticaria appeared earlier after immunotherapy, while keratoacanthoma appeared later. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 23 ] A Korean retrospective analysis found that melanoma and genitourinary malignancies were most likely to experience cutaneous adverse reactions following the use of PD-1/PD-L1 inhibitors; pruritic, psoriatic, and urticaria are the most common types of rash, with median times of appearance of 15, 20, and 6.5 weeks respectively; urticaria appeared earlier after immunotherapy, while keratoacanthoma appeared later. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…[23] A Korean retrospective analysis found that melanoma and genitourinary malignancies were most likely to experience cutaneous adverse reactions following the use of PD-1/PD-L1 inhibitors; pruritic, psoriatic, and urticaria are the most common types of rash, with median times of appearance of 15, 20, and 6.5 weeks respectively; urticaria appeared earlier after immunotherapy, while keratoacanthoma appeared later. [24] A retrospective analysis of tislelizumab in combination with gemcitabine plus cisplatin as first-line treatment for locally advanced or metastatic BCa suggested that the most common TRAEs were anemia (57.1%), decreased appetite (57.1%), nausea/vomiting (50.0%), and thyroid disorders (42.9%). The reported rate of rash was 14.3%.…”
Section: Not Sure or N/a Yes Notmentioning
confidence: 99%
“…More than 88% [4][5][6] TKIs Gefitinib, erlotinib, lapatinib, afatinib 43%-75% 4,5,7,8 Her2 inhibitor Trastuzumab,pertuzumab about25% 9 VEGFRI Bevacizumab, aflibercept present RAS / RAF / MEK / ERK inhibitor BRAF inhibitor Vemurafenib,dabrafenib 3%-9% 10,11 MEK inhibitor Trametinib 74%-89% 11,12 Combination of BRAF and MEK inhibitors 14%-40% 11,13 Multikinase inhibitors Sorafenib, sunitinib Present 10 mTOR inhibitor Everolimus, sirolimus 15%-49% 12 PD-1/PD-L1 inhibitor Nivolumab, Pembrolizumab 0.3%-8% 8,14,15 CTLA-4 inhibitor Ipilimumab, tremelimumab 2.4%-7.3% 16 Note: Present = event has been reported, but the frequency is unknown. As BRAF, MEK, and mTOR are all downstream molecules of EGFR signaling, inhibition of these molecules can result in similar reactions.…”
Section: Egfri Monoclonal Antibodies Cetuximab,panitumumabmentioning
confidence: 99%